Define the type of given PDE and find the solution. (y^2+z^2-x^2 )p+2xyq+2zx=0
Given differential equation is "(y^2+z^2-x^2 )p+2xyq+2zx=0"
Then we can write,
"\\frac{dx}{(y^2+z^2-x^2 )}=\\frac{dy}{2xy}=\\frac{dz}{-2zx}"
Taking last two terms,
"\\frac{dy}{2xy}=\\frac{dz}{-2zx}"
Integrating both sides, we get
"\\int\\frac{dy}{y}=\\int \\frac{dz}{-z}"
"log |y| = -log|z| + logC_1 \\implies yz = C_1" (1)
then "z = \\frac{C_1}{y}"
taking first two terms,
"\\frac{dx}{(y^2+z^2-x^2 )}=\\frac{dy}{2xy}"
putting value of z from equation (1),
"\\frac{dx}{(y^2+\\frac{C_1^2}{y^2}-x^2 )}=\\frac{dy}{2xy}"
"{(y^2+\\frac{C_1^2}{y^2}-x^2 )}{dy}={2xy}{dx}"
"{2xy}{dx} - {(y^2+\\frac{C_1^2}{y^2}-x^2 )}{dy} = 0" (2)
This equation is exact differential equation, as
"\\frac{\\partial M}{\\partial y} = \\frac{\\partial N}{\\partial x} = 2x"
where "M ={2xy}, N = - {(y^2+\\frac{C_1^2}{y^2}-x^2 )}"
then integrating both sides equation (2),
"\\int{2xy}{dx} - \\int{(y^2+\\frac{C_1^2}{y^2}-x^2 )}{dy} = C_2"
"x^2y-\\frac{y^3}{3}+\\frac{C_1^2}{y} = C_2"
putting value of "C_1"
"x^2y-\\frac{y^3}{3}+yz^2 = C_2" (3)
Hence equation (1) and (3) are the required solutions of the equation.
Comments
Leave a comment